Internal Radiation Monitoring of Occupational Staff in Nuclear Medicine Facility - Ferdous, MJ; Alam, Z; Khan, RK; Iqubal, SM; Islam, A; Rahman, MA; Begum, Aleya (Bangladesh Journal of Medical Physics, 2013)
Unsealed radioactive sources used in Nuclear Medicine Centers, to diagnose and treat patients, pose significant risks of internal exposure to the occupational staff. This work intends to evaluate the potential risks of internal contamination of occupational staff in Nuclear Medicine facilities. 49 urine samples of 19 occupational staff working in the two busiest nuclear medicine centres, namely Institute of Nuclear Medicine and Ultrasound (INMU) and Centre of Nuclear Medicine and Ultrasound (CNMU) Dhaka, were collected to perform this study. The concentrations of 99mTc and 131I in urine samples were measured using a High Purity Germanium (HPGe) detector. The radioactivity of 99mTc and 131I were found to be 8.58±0.03 Bql-1 to 314±1.92 Bql-1 and from 6.47±0.03 Bql-1 to 283±0.27 Bql-1 respectively. The effective doses of occupational staff have also been calculated using the radioactivity concentration and the dose coefficients. Due to the highest (314 Bql-1) and the lowest (8.58Bql-1) concentration of 99mTc, the effective doses were 14.7 ?Sv and 0.402?Sv, on the other hand for the highest (283 Bql-1) and the lowest (6.47 Bql-1) concentration of 131I, the effective doses were 5.58 ?Sv and 0.12 ?Sv. These values are within limits, however to avoid inhalation and contamination of 131I and 99mTc proper working environment should be established with suitable ventilation system, fume hood, mask, etc. DOI: http://dx.doi.org/10.3329/bjmp.v5i1.14670 Bangladesh Journal of Medical Physics Vol.5 No.1 2012 63-70